Eocene adakitic quartz monzonites and granite porphyries from the northern Qiangtang Block, central Tibet: Partial melting of sediment-rich mélange? - Xu, Chuan-Bing; Zeng, Ji-Peng; Wang, Qiang; Zhang, Xiu-Zheng; Ou, Quan; Wang, Jun; Hao, Lu-Lu; Chen, Yiwei (Frontiers in Earth Science, 2022)
The timing and mechanism of crustal thickening and initial surface uplift of the Tibetan Plateau remain disputed. Here, we report zircon U–Pb geochronological and O isotopic and whole-rock geochemical and Sr–Nd isotopic data for Eocene (41–37 Ma) granite porphyries and quartz monzonites from the Qoima Co area of the northern Qiangtang Block, central Tibet. The granite porphyries are characterized by high silica content (72 wt%), adakitic trace-element compositions, enriched Sr–Nd isotope signatures [(87Sr/86Sr)i = 0.7074, εNd (t) = −4.5], and a mean zircon δ18O value of +6.28 ± 0.85‰. The quartz monzonites exhibit high K2O content (5.1–6.8 wt%) and K2O/Na2O ratios (1.3–2.3). They also display adakitic geochemical characteristics, such as low Y (12–25 ppm) and Yb (1.1–1.8 ppm) content, high Sr/Y (98–187) and La/Yb (59–134) ratios, negligible Eu and positive Sr anomalies, and depletion in Nb and Ta. The quartz monzonites have (87Sr/86Sr)i ratios ranging from 0.7069 to 0.7078, εNd (t) values of −5.1 to −2.9, and mean δ18O values ranging from +6.27 ± 0.64‰ to +7.91 ± 0.32‰. We suggest that the granite porphyries were most probably derived by the partial melting of thickened, sediment-bearing lower crust and that the quartz monzonites were most likely generated by the partial melting of sediment-rich mélange. Combining these results with the existing tectonic and geophysical data, we conclude that continental subduction and mélange underplating may have been responsible for crustal shortening and tectonic thickening.